Komunikasi Lintas Budaya: Konsep, Tantangan, Dan Strategi Pengembangannya - Mudrik, Nizar; Irsyad Fawwaz, Zhaldi Enji (IAINU Kebumen, 2024)
Cross-cultural communication refers to the process of interaction between individuals or groups from different cultural backgrounds, aimed at fostering mutual understanding. In the era of globalization, this ability has become increasingly essential to support international collaboration, build harmonious relationships, and overcome barriers caused by differences in language, values, and social norms. This article explores the fundamental concepts of cross-cultural communication, key challenges such as language barriers and stereotypes, and strategies to enhance its effectiveness. Research highlights that high-context and low-context cultures exhibit distinct communication patterns, requiring adjustments in message delivery. Cross-cultural education, the development of active listening skills, and the use of cultural mediators are strategic measures to address these challenges. Moreover, effective cross-cultural communication contributes to increased innovation, collaboration, and inclusivity across various sectors, particularly in business and education. By understanding the dynamics of diverse cultures, individuals and organizations can create more harmonious and productive interactions. This article emphasizes that cross-cultural communication is a critical skill for navigating the complexities of an increasingly interconnected global world.